Analisis Komunikasi Video Tutorial Make Up Beauty Vlogger Indira Kalistha - Reni Nur Fadila; Suryati; Manalullaili (STID Raudlatul Iman Sumenep, 2023)
This study aims to determine the persuasive communication techniques used by Indira Kalistha when giving make-up tutorials on her Youtube. This study uses a qualitative approach with Roland Barthesâ€™s semiotic aanalysis known as the â€œtwo orders of significationâ€, including denotation and connotation. In this study using the theory of persuasive communication techniques quoted from the book on communication Dynamics by Onong Uchjana Effendy which is the main theory of problem solving. The results of this study indicate that there are five persuasive communication techniques used by Indira Kalistha in the video entitled Make Up For Teenagers in the capital city under 100k!instantly beautiful and no cut no edit make up tutorials for lebaran under 100k, namely association techniques, integration techniques, reward techniques, setting technique and red hearing technique. Penelitian ini bertujuan untuk mengetahui teknik komunikasi persuasif yang digunakan oleh Indira Kalistha saat memberikan tutorial make up di youtub-nya. Penelitian ini menggunakan metode pendekatan kualitatif dengan analisis semiotika Roland Barthes yang dikenal dengan â€œtwo order of significationâ€, mencakup denotasi dan konotasi.Dalam penelitian ini menggunakan teori teknik komunikasi persuasif yang dikutip dari buku Dinamika Komunikasi karya Onong Uchjana Effendy yang menjadi teori utama pembedah masalah. Hasil penelitian ini menunjukan adanya kelima teknik komunikasi persuasif yang digunakan oleh Indira Kalistha dalam video yang berjudul Make Up Remaja Ibu Kota Under 100k!Auto Cakep Dan No Cut No Edit Make Up Tutorial Lebaran Dibawah 100 Ribu, yaitu teknik asosiasi, teknik integrasi, teknik ganjaran, teknik tataan, dan teknik red hearing.